Federalism and the optimal degree of centralization of public goods - Martin Kolmar (Brown University, Department of Economics, 2001)
In this paper we analyze the optimal degree of centralization for the supply of public goods. We identify the reliance on an exclusion mechanism as a central feature of the decentralized provision of public goods. An exclusion mechanism induces a contest between users of the public goods who want to free ride and the providers who want to exclude free riding. This contest explains the costs of decentralization. A centralized contribution does not rely on an exclusion mechanism to finance the public goods but on taxation which induces different types of transaction costs. A comparison of the relevant distortions explains the optimal degree of centralization of the supply of public goods.
Keywords: D74; H41; H70; K42; 330; Public Goods; Club Goods; Contests; Fiscal Federalism; Öffentliches Gut; Dezentralisierung; Finanzföderalismus; Theorie